(untitled) (Research, Society and Development, 2023)
Hospital infection is an infectious syndrome that can manifest itself during hospitalization and is related to some intra-hospital factors, such as incorrect handling of some materials. The objective of this study was to address aspects that guide the importance of health professionals, with emphasis on the role of professional nurses in the care of patients with hospital infections. This is a literature review, in which 2,547 works were found. From the study, it is possible to observe that the use of PPE by health professionals is essential, with a view to protecting the nurse and, subsequently, preventing the spread of infections to the patient. In addition, research has shown that the number of patients who acquire the infection becomes significantly higher, 50%, when the number of professionals is not proportional to the number of patients, taking into account the overload and lack of trained people. In view of this, it is worth noting that continuing education is relevant in this matter, as it is important that nurses are always up to date on the various diseases, their control and treatment. It was observed that patient safety must be taken from preventive measures in the hospital environment. However, due to the great demand and lack of time for professionals, these prevention methods, on several occasions, do not show promising results.